Dynamic Mathematical Modeling and Simulation Study of Small Scale Autonomous Hovercraft - Mohd Zamzuri, Ab Rashid; M. S. M.`, Aras; Mohd Azmin, Kassim; Zawawi, Ibrahim; Annisa, Jamali (Science & Engineering Research Support soCiety, 2012)
Nowadays, various mechanical, electrical systems or combination of both systems are used tohelp or ease human beings either during the daily life activity or during the worst condition faced by them. The system that can be used to increase human life quality are such as in military operations, pipeline survey, agricultural operations and border patrol. The worst condition that normally faced by human are such as earthquake, flood, nuclear reactors explosion and etc. One of the combinations of both systems is unmanned hovercraft system which is still not thoroughly explored and designed. Hovercraft is a machine that can move on the land surface or water and it is supported by cushion that has high compressed air inside. The cushion is a close canvas and better known as a skirt. A hovercraft moves on most of surfaces either in rough, soft or slippery condition will be developed. The main idea for this project is to develop a dynamic modelling and controller for autonomous hovercraft. The model of the hovercraft will be initially calculated using Euler Lagrange method. The model of the hovercraft is derived using Maple software. The model that is developed then needs to be tested with open loop simulation in the MATLAB/Simulink environment. The LQR controller to regulate the small scale autonomous hovercraft then will be developed and tested with MATLAB.